PENINGKATAN LITERASI KESEHATAN REMAJA TENTANG BAHAYA MEROKOK MELALUI KEGIATAN SOSIALISASI DI LINGKUNGAN SEKOLAH - Nur Hamida Siregar; Purnama Helena Hutabarat (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
Limited knowledge and awareness about the dangers of smoking often contribute to the early adoption of smoking habits among students. Therefore, educational initiatives are needed to increase students’ understanding of the risks associated with smoking. This community service activity was conducted through a health education program for students in a school setting using lectures, presentations, and interactive discussions. The materials covered the harmful substances in cigarettes, the health impacts of smoking, and preventive strategies to avoid smoking behavior. The results indicated that the activity improved students’ knowledge and awareness of the dangers of smoking and encouraged them to adopt healthier life styles. Students also demonstrated active participation during the discussion session. These findings suggest that health education programs can be an effective approach to preventing smoking behavior among adolescents.